The instrumentalist - Constable, Harriet (Simon & Schuster, 2024)
"A stunning debut novel of music, intoxication, and betrayal inspired by the true story of Anna Maria della Pietà, a Venetian orphan and violin prodigy who studied under Antonio Vivaldi and ultimately became his star musician--and his biggest muse."--